Assessment and conceptualization of perceived competence in ice hockey: a scale development and validation study - Pelletier, V. H.; Lemoyne, J. (Perceptual and Motor Skills, 2023)
Perceived competence plays a crucial role in establishing environments favorable to individual development in youth sport. As most assessment tools of perceived competence are not sport-specific, they have limited usefulness for sport practitioners and researchers. This study had two-fold aims: (i) to develop a perceived competence assessment tool specific to ice hockey; and (ii) to examine its factorial structure and internal consistency. We first developed an initial 29-item version of this ice hockey competence self-report scale, using a group of ice hockey stakeholders and sports science experts to develop the items and a pilot sample of 42 hockey players to confirm test-retest reliability. Finally, we validated the scale among a cohort of 770 adolescent ice hockey players (M age = 14.78, SD = 1.60 years). Results from exploratory factor analysis (EFA) revealed that perceived competence in ice hockey was defined by six dimensions, with rejection of seven items. Confirmatory factor analysis (CFA) suggested that the 6-factor first order model was the best fit with the conceptualization of perceived competence in ice hockey (CFI = 0.938, RMSEA = 0.044). The final, 22-item questionnaire now provides a reliable and valid measure of perceived competence in hockey for adolescent participants. It has promise for evaluating future interventions aiming to foster young athletes` perceived confidence through sport.